Deep processes and indigenous diamond deposits - V. V. Gordienko (Геофизический журнал, 2013)
Processes of formation and transportation of kimberlite magma and diamonds in the upper mantle and the Earth's crust have been considered. Analysis corresponds to the ideas of advec-tion-polymorph hypothesis. The Klifford rule has been considered, the depth of the main diamond generation and the depth of primary source of magma have been identified.